Shadow Sovereign Ratings for Unrated Developing Countries - Ratha, Dilip (2012)
We predict sovereign ratings for developing countries that do not have risk ratings from agencies such as Fitch, Moody's, and Standard and Poor's. Ratings are important in determining the volume and cost of capital flows to developing countries through international bond, loan, and equity markets. Sovereign rating also acts as a ceiling for the foreign currency rating of sub-sovereign borrowers and can be important for their access to international debt and equity capital. We generate shadow ratings for several developing countries that have never been rated and find that unrated countries are not always at the bottom of the rating spectrum. Several of them are projected to have a "B" or higher rating, in a similar range to that of the emerging market economies with capital market access.